Novel green and environment-friendly magnesium air battery anode material and preparation method thereof
Through the alloying design and preparation method of Ga and Sn elements, the composition and structure of the anode material of magnesium air battery is optimized, and the self-discharge and passivation layer of the anode material of magnesium air battery is solved, the stability and efficiency of the battery are improved, and the More efficient energy conversion and longer battery life.
Patent Information
- Application Number
- CN202411219061.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
The existing magnesium air battery anode materials are prone to side reactions in the electrolyte and lead to serious self-discharge, and a passivation layer is formed on the surface of the magnesium anode, which affects the stability and efficiency of the battery.
The magnesium anode material is prepared by alloying using Ga and Sn elements. It is optimized through alloy composition design and preparation methods, including alloy preparation in induction heating furnace, stirring and mold casting, low-temperature treatment, multi-directional forging and aging treatment, forming high discharge activity and corrosion-resistant properties of magnesium air battery anode material.
It significantly improves the electrochemical performance and service life of magnesium air batteries, reduces environmental pollution, enhances the efficiency and corrosion resistance of the anode, and achieves more efficient energy conversion and longer battery life.
Abstract
Description
Technical Field
[0001] The invention relates to a novel green and environmentally friendly magnesium-air battery anode material and a preparation method thereof, belonging to the technical field of industrial magnesium alloy materials. Background Art
[0002] As a green energy storage device with great application prospects, magnesium-air batteries have attracted widespread attention in recent years due to their advantages such as high theoretical energy density, high abundance and environmental friendliness. Among the many components of magnesium-air batteries, the anode material plays a vital role and directly affects the overall performance and service life of the battery. The anode material of magnesium-air batteries is mainly pure magnesium or magnesium alloy. Although it has a high theoretical capacity and good electrochemical activity, there are still many problems in practical applications, including the side reactions in the electrolyte that lead to serious self-discharge, or the formation of a passivation layer on the surface of the magnesium anode when the battery is running, which affects the stability and efficiency of the battery.
[0003] At present, the anode materials of magnesium-air batteries with relatively mature applications are mainly Mg-Hg-Ga systems, which have high battery efficiency and have been applied in some fields. Among them, the alloy material invented by Professor Wang Richu's team at Central South University has good comprehensive performance. It is worth noting that the preparation of alloys in this system requires special processes, and because of the presence of Hg, there are biosafety risks throughout the life cycle.
[0004] In recent years, researchers have been committed to developing new green anode materials for magnesium-air batteries, aiming to improve the overall performance of batteries by improving the electrochemical properties and stability of the materials. These new anode materials usually include magnesium-based alloys, magnesium composites, and surface-modified magnesium materials. For example, by introducing an appropriate amount of alloying elements (such as Al, Zn, Sn, etc.) into the magnesium matrix, the electrochemical activity of the anode can be effectively regulated, the occurrence of side reactions can be inhibited, and the mechanical strength and corrosion resistance of the material can be enhanced. On the other hand, magnesium composites can not only improve the conductivity of the anode by incorporating conductive additives such as carbon nanotubes, graphene or metal oxides into the magnesium matrix, but also promote the oxygen reduction reaction, thereby improving the energy conversion efficiency of the battery. In addition, the surface of the magnesium anode is modified by chemical or electrochemical methods to form a stable protective film, which can effectively prevent the electrolyte from corroding magnesium, thereby extending the cycle life of the battery.
[0005] In summary, the development of green and efficient anode materials is the key to the technological progress of magnesium-air batteries. Through material innovation and surface modification, the electrochemical performance of batteries can be significantly improved, environmental pollution can be reduced, and magnesium-air batteries can be promoted to be more efficient, environmentally friendly and economical. Future research directions will focus on further optimizing the composition and structure of anode materials, exploring more advanced surface modification technologies and battery system integration solutions, in order to achieve the widespread application of magnesium-air batteries in large-scale energy storage and portable power sources. Summary of the invention
[0006] The purpose of the present invention is to provide a new green and environmentally friendly magnesium-air battery anode material with certain corrosion resistance and high discharge activity, and to develop a new anode material through alloy composition design.
[0007] Another object of the present invention is to provide a method for preparing the magnesium-air battery anode material.
[0008] To achieve the above object, the present invention adopts the following technical solutions: A novel green and environmentally friendly magnesium-air battery anode material. The anode material comprises, by weight percentage, 1.0-5.0% Ga, 0.5-5.0% Sn, 0-3.0% In, and the remainder Mg, wherein the content of impurity elements is controlled to be: Fe<0.01%, Ni<0.01%, and Cu<0.01%.
[0009] Preferably, the anode material comprises, by weight percentage, Ga 2.0-4.0%, Sn 1.0-2.0%, In 1.0-2.0%, and the remainder Mg.
[0010] A method for preparing the magnesium-air battery anode material comprises the following steps: (1) Alloy preparation is carried out in an induction heating furnace. Mg and Sn are added in the form of pure metals. Under the atmosphere of protective gas, the temperature is raised to between 690 and 710 °C. After all the additives are melted, Mg-Ga and Mg-In master alloys are added and stirring is continued. The temperature is controlled between 720 and 740 °C and the stirring time is controlled between 10 and 20 min. (2) After stirring, pour it into the mold, further cool the mold to 600~650℃, then cool it rapidly to 350~400℃, and then keep it warm for 5~24h. The purpose is to achieve uniform distribution of elements and reduce microsegregation. After the insulation is completed, quickly cool it to room temperature with water, and remove the mold to obtain an ingot.
[0011] Preferably, in step (1), during the smelting and stirring process, ceramic balls with a size of 2 to 5 mm and high-temperature alloy balls with a size of 2 to 5 mm are added, and the two kinds of balls are mixed in a volume ratio of 1:1. Before adding, they are cleaned with ultrasonic-alcohol to remove surface dust, and then dried and heated to 300°C.
[0012] Preferably, in step (1), electromagnetic stirring is used to quickly stir the melt to achieve uniform distribution of the elements. After stirring, the melt is filtered to completely separate the added small balls, and then poured into a mold with a diameter of 250-300 mm and a height of 700-900 mm.
[0013] Preferably, the preparation method of the Mg-Ga master alloy or the Mg-In master alloy comprises the following steps: ① Drill holes with a diameter of 10-30 mm evenly in the magnesium ingot, heat the metal Ga to 30-40°C or heat the metal In to 150-160°C, and inject it into the hole. At the same time, plug the hole with a magnesium wire with a diameter of 3-5 mm, tighten the magnesium plug, and wrap the raw tape between the magnesium plug and the magnesium ingot to prevent Ga or In from leaking out. Then put it in a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 10 -3 ~10 -4 Between Pa; ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 180~200℃, keep warm for 1~5h, continue to heat to 350~400℃, keep warm for 0.5~1h, continue to heat to 650~700℃, keep warm for 0.5~1h, quickly turn the vacuum tank over and shake it for 10~30min, and cool it in 25±1℃ water; ③ The completely cooled vacuum tank is demolded to obtain a Mg-Ga intermediate alloy or a Mg-In intermediate alloy.
[0014] Preferably, the Ga content in the Mg-Ga master alloy is 20-30%; the In content in the Mg-In master alloy is 20-30%.
[0015] Preferably, the method for preparing the magnesium-air battery anode material further comprises the following steps: (3) Place the ingot in liquid nitrogen for low-temperature treatment, and apply direct current intermittently. The intermittent time is controlled within 5-10 minutes, and the power-on time each time does not exceed 5 minutes. The voltage is controlled between 100-220V. Keep the ingot under the temperature difference between the inside and outside for 30-60 minutes, and then quickly move it to room temperature. (4) The ingot is further heated to between 200 and 350 °C, and then multi-directional forging is performed, followed by direct extrusion to ensure that the material is a completely deformed structure. The extruded material can be a plate, a bar or other profiles.
[0016] If it is a plate, subsequent rolling can be carried out, the plate temperature is controlled at 150~300℃, the rolling reduction is controlled between 30~80%, the roller temperature is controlled at 70~100℃ during the rolling process, and graphite powder or molybdenum disulfide is applied on the rolling surface to achieve a lubrication effect.
[0017] The aging treatment of the deformed material includes the following steps: (5) First, the profile is pre-stretched and straightened, and the total deformation is controlled between 3% and 5%. Under the premise of maintaining the shape, enough dislocations are constructed to facilitate subsequent precipitation. At the same time, after pre-stretching 10-15% of the yield strength, it is energized and alternately loaded with pulse current and direct current. The different heating principles of the two are used to achieve the nucleation and growth of the strengthening phase precipitation. The alternating loading time is controlled within 10-30 minutes; (6) Then carry out aging treatment, the system is to keep the temperature at 60~80℃ for 24~48h, then increase the temperature to 120~150℃ and keep it for 10~20h, increase the temperature to 180~200℃ and keep it for 10~20h, then cool down to 90~100℃ and keep it for 3~5h; (7) For the plate, a final cold pressing deformation is performed to control the shape of the plate, and the deformation is controlled between 1 and 3%, and then it is rolled.
[0018] The beneficial effects of the present invention are: 1. The use of green elements Ga and Sn to alloy the magnesium anode can reduce environmental pollution during the use of air batteries and the high recycling cost.
[0019] 2. Low alloy anodes can improve the quality-to-energy advantage and increase the service life of the equipment.
[0020] 3. Ga and Sn elements have a dissolution and re-deposition effect during the discharge process, which destroys the surface passivation film and improves the anode efficiency. At the same time, Sn can refine the grain size, promote uniform distribution of components, and reduce the corrosion rate of the alloy. Through experimental tests, the above magnesium alloy material has high electrochemical activity and reduces the self-corrosion rate.
[0021] 4. By introducing the In element, the battery efficiency can be effectively improved.
[0022] 5. The Mg-Ga master alloy is prepared by sealed smelting, and the Ga element is added in the form of the master alloy, which greatly improves the yield of the Ga element.
[0023] 6. The advanced preparation method includes the introduction of a two-component stirring ball to achieve micro-segregation of elements, low temperature + power treatment of ingots to eliminate casting stress, auxiliary DC and AC power under pre-stress conditions to achieve residual stress reduction and control of nucleation and growth of precipitate phases, and the use of four-stage aging heat treatment to achieve uniform precipitation of strengthening phases. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the embodiments.
[0025] Example 1 A new type of green and environmentally friendly cast Mg-1.2Ga-0.5Sn (by weight percentage, the composition is: Ga1.2%, Sn 0.5%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes with a diameter of 10 mm evenly in the magnesium ingot, inject metal Ga at 30°C into the holes, and insert magnesium wire with a diameter of 3 mm into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it in a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 2.1×10 -4 Pa.
[0026] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 180±5℃, keep warm for 1.5h, continue to heat to 350±5℃, keep warm for 0.5h, continue to heat to 650±5℃, keep warm for 0.5h, quickly flip and shake the vacuum tank for 10min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-20Ga master alloy (by weight percentage, the composition is: Ga 20%, the rest is Mg).
[0027] ③ Add Mg and Sn pure metals in the induction heating furnace, and raise the temperature to 690±5℃ in the atmosphere of protective gas. After all the additives are melted, add Mg-20Ga master alloy, 2mm ceramic balls and 2mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 720±5℃ and the stirring time is 10min. After stirring, it is filtered and poured into a mold with a diameter of 250mm and a height of 800mm, and then cooled to 600±5℃.
[0028] ④ The mold is rapidly cooled to 350±5℃, then kept warm for 5 hours, quickly water-cooled to room temperature, and the ingot is obtained after the mold is removed.
[0029] The constant current discharge curve test was carried out at room temperature and pressure. 2At the current density of 100 mA / cm, the average discharge potential is -1.60 V and the anode efficiency is 62.66%. 2 Under the current density, the average discharge potential is -1.38V, and the anode efficiency is 70.30%. The corrosion rate is 0.05mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0030] Example 2 A new type of green and environmentally friendly extruded Mg-1.5Ga-1.0Sn-0.5In (by weight percentage, the composition is: Ga 1.5%, Sn 1.0%, In 0.5%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes of 12 mm in diameter evenly in the magnesium ingot, inject metal Ga at 32.5°C and metal In at 155.5°C into the holes respectively, and insert magnesium wire of 3.5 mm in diameter into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 5.2×10 -4 Pa.
[0031] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 185±5℃, keep warm for 2h, continue to heat to 355±5℃, keep warm for 0.5h, continue to heat to 655±5℃, keep warm for 0.5h, quickly flip and shake the vacuum tank for 20min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-25Ga (by weight percentage, the composition is: Ga 25%, the rest is Mg) and Mg-25In (by weight percentage, the composition is: In25%, the rest is Mg) intermediate alloys.
[0032] ③ Add Mg and Sn pure metals in the induction heating furnace, and raise the temperature to 695±5℃ in the atmosphere of protective gas. After all the additives are melted, add Mg-25Ga and Mg-25In master alloys, 2.5mm ceramic balls and 2.5mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 725±5℃ and the stirring time is 12min. After stirring, filter and pour into a mold with a diameter of 255mm and a height of 800mm, and then cool to 620±5℃.
[0033] ④ The mold is rapidly cooled to 355±5℃, then kept warm for 10 hours, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is intermittently applied at the same time. The intermittent time is 5 minutes, and the power-on time is 5 minutes each time. The control voltage is 110V. The ingot is kept under the internal and external temperature difference for 30 minutes, and then quickly moved to room temperature. The ingot is further heated to 200±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by extrusion at 420±5℃, with an extrusion ratio of 23:1, to obtain the extruded Mg-1.5Ga-1.0Sn-0.5In magnesium air battery anode material.
[0034] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.65 V and the anode efficiency is 63.52%. 2 At the current density, the average discharge potential is -1.45V, and the anode efficiency is 73.1%. The corrosion rate is 0.05 mg·cm according to GBT10123-2022 test at room temperature and pressure (25°C, standard atmospheric pressure). -2 ·h -1 .
[0035] Example 3 A new type of green and environmentally friendly extruded Mg-1.5Ga-1.5Sn (by weight percentage, the composition is: Ga1.5%, Sn 1.5%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe<0.01%, Ni<0.01%, Cu<0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes with a diameter of 12 mm evenly in the magnesium ingot, inject metal Ga at 30°C into the holes, and insert magnesium wire with a diameter of 4 mm into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it in a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 4.7×10 -4 Pa.
[0036] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 190±5℃, keep warm for 3h, continue to heat to 360±5℃, keep warm for 1h, continue to heat to 660±5℃, keep warm for 1h, quickly flip and shake the vacuum tank for 25min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-30Ga master alloy (by weight percentage, the composition is: Ga 30%, the rest is Mg).
[0037] ③ Add Mg and Sn pure metals in the induction heating furnace, and raise the temperature to 700±5℃ in the atmosphere of protective gas. After all the additives are melted, add Mg-30Ga master alloy, 2mm ceramic balls and 2mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 730±5℃ and the stirring time is 15min. After stirring, filter and pour into a mold with a diameter of 260mm and a height of 800mm, and then cool to 625±5℃.
[0038] ④ The mold is rapidly cooled to 360±5℃, then kept warm for 12h, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is intermittently applied at the same time. The intermittent time is 8min, the power-on time is 4min each time, and the control voltage is 150V. The ingot is kept under the internal and external temperature difference for 40min, and then quickly moved to room temperature. The ingot is further heated to 240±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by extrusion at 425±5℃, with an extrusion ratio of 30:1, to obtain the extruded Mg-1.5Ga-1.5Sn magnesium air battery anode material.
[0039] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.62 V and the anode efficiency is 64.72%. 2 Under the current density, the average discharge potential is -1.40V, and the anode efficiency is 70.04%. The corrosion rate is 0.07mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0040] Example 4 A new type of green and environmentally friendly rolled Mg-2.0Ga-1.0Sn (by weight percentage, the composition is: Ga2.0%, Sn 1.0%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes of 15 mm in diameter evenly in the magnesium ingot, inject metal Ga at 30°C into the holes, and insert magnesium wire of 5 mm in diameter into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 5.1×10 -4 Pa.
[0041] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 200±5℃, keep warm for 3h, continue to heat to 370±5℃, keep warm for 1h, continue to heat to 670±5℃, keep warm for 1h, quickly flip and shake the vacuum tank for 30min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-20Ga master alloy (by weight percentage, the composition is: Ga 20%, the rest is Mg).
[0042] ③ Add Mg and Sn pure metals in the induction heating furnace, raise the temperature to 700±5℃ in the atmosphere of protective gas, and after all the additives are melted, add Mg-20Ga master alloy, 3mm ceramic balls and 3mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 740±5℃ and the stirring time is 20min. After stirring, filter and pour into a mold with a diameter of 270mm and a height of 800mm, and then cool to 630±5℃.
[0043] ④ The mold is rapidly cooled to 350±5℃, then kept warm for 14h, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is intermittently applied at the same time. The intermittent time is 5min, the power-on time is 2min each time, and the control voltage is 180V. The ingot is kept under the internal and external temperature difference for 30min, and then quickly moved to room temperature. The ingot is further heated to 250±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by 425±5℃ extrusion, and an extrusion ratio of 27:1.
[0044] ⑤ Rolling after extrusion, the rolling process temperature is 200±5℃, the rolling reduction is 30%, the roller temperature during rolling is 100±5℃, graphite powder or molybdenum disulfide is applied on the rolling surface, and the rolled Mg-2.0Ga-1.0Sn magnesium air battery anode plate is obtained after three rolling passes.
[0045] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.68 V and the anode efficiency is 66.02%. 2 Under the current density, the average discharge potential is -1.50V, and the anode efficiency is 80.11%. The corrosion rate is 0.03mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0046] Example 5 A new type of green and environmentally friendly rolled Mg-2.0Ga-2.0Sn-1.0In (by weight percentage, the composition is: Ga 2.0%, Sn 2.0%, In 1.0%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes of 20 mm in diameter evenly in the magnesium ingot, inject metal Ga at 37.5°C and metal In at 157.5°C into the holes respectively, and insert magnesium wire of 3.5 mm in diameter into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 4.4×10 -4 Pa.
[0047] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 190±5℃, keep warm for 5h, continue to heat to 375±5℃, keep warm for 0.5h, continue to heat to 675±5℃, keep warm for 0.5h, quickly flip and shake the vacuum tank for 25min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-25Ga (by weight percentage, the composition is: Ga 25%, the rest is Mg) and Mg-25In (by weight percentage, the composition is: In 25%, the rest is Mg) intermediate alloys.
[0048] ③ Add Mg and Sn pure metals in the induction heating furnace, and raise the temperature to 705±5℃ in the atmosphere of protective gas. After all the additives are melted, add Mg-25Ga and Mg-25In master alloys, 3.5mm ceramic balls and 3.5mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 725℃ and the stirring time is 18min. After stirring, it is filtered and poured into a mold with a diameter of 290mm and a height of 800mm, and then cooled to 640±5℃.
[0049] ④ The mold is rapidly cooled to 370±5℃, then kept warm for 18h, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is applied intermittently with an interval of 8min, a power-on time of 4min each time, and a control voltage of 200V. The ingot is kept at the internal and external temperature difference for 40min, and then quickly moved to room temperature. The ingot is further heated to 280±5℃, and then subjected to three passes of multi-directional forging, with a deformation of 50% in each pass, followed by extrusion at 430±5℃ with an extrusion ratio of 32:1.
[0050] ⑤ Rolling after extrusion, the rolling process temperature is 220±5℃, the rolling reduction is 33%, the roller temperature during rolling is 90±5℃, graphite powder or molybdenum disulfide is applied on the rolling surface, and the rolled Mg-2.0Ga-2.0Sn-1.0In magnesium air battery anode plate is obtained after two rolling passes.
[0051] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.69 V and the anode efficiency is 66.34%. 2 At the current density, the average discharge potential is -1.51V, and the anode efficiency is 80.19%. The corrosion rate is 0.05mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0052] Example 6 A novel green and environmentally friendly aged Mg-2.0Ga-3.0Sn (by weight percentage, the composition is: Ga2.0%, Sn 3.0%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes with a diameter of 25 mm evenly in the magnesium ingot, inject metal Ga at 39°C into the holes, and insert magnesium wire with a diameter of 4.5 mm into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 3.6×10 -4 Pa.
[0053] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 195±5℃, keep warm for 4.5h, continue to heat to 380±5℃, keep warm for 1h, continue to heat to 680±5℃, keep warm for 1h, quickly flip and shake the vacuum tank for 20min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-30Ga master alloy (by weight percentage, the composition is: Ga 30%, the rest is Mg).
[0054] ③ Add Mg and Sn pure metals in the induction heating furnace, and raise the temperature to 705±5℃ in the atmosphere of protective gas. After all the additives are melted, add Mg-30Ga master alloy, 4mm ceramic balls and 4mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 730±5℃ and the stirring time is 20min. After stirring, filter and pour into a mold with a diameter of 280mm and a height of 800mm, and then cool to 645±5℃.
[0055] ④ The mold is rapidly cooled to 380±5℃, then kept warm for 20 hours, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is applied intermittently at the same time. The interval time is 5 minutes, and the power-on time is 3 minutes each time. The control voltage is 220V. The ingot is kept under the temperature difference between the inside and the outside for 50 minutes, and then quickly moved to room temperature. The ingot is further heated to 300±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by extrusion at 415±5℃ with an extrusion ratio of 30:1. The profile is pre-stretched and straightened, with a total deformation of 3%.
[0056] ⑤ The aging treatment was set to 80±5℃ for 24h, then heated to 120±5℃ for 10h, heated to 180±5℃ for 10h, then cooled to 100±5℃ for 5h. The aged Mg-2.0Ga-3.0Sn magnesium air battery anode plate was obtained.
[0057] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.70 V and the anode efficiency is 66.39%. 2 Under the current density, the average discharge potential is -1.52V, and the anode efficiency is 80.57%. The corrosion rate is 0.09mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0058] Example 7 A novel green and environmentally friendly aged Mg-3.0Ga-2.0Sn-1.0In (by weight percentage, the composition is: Ga 3.0%, Sn 2.0%, In 1.0%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes of 30 mm in diameter evenly in the magnesium ingot, inject metal Ga at 40°C and metal In at 160°C into the holes respectively, and insert magnesium wire of 5 mm in diameter into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 4.3×10 -4 Pa.
[0059] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 200±5℃, keep warm for 3h, continue to heat to 385±5℃, keep warm for 0.5h, continue to heat to 685±5℃, keep warm for 0.5h, quickly flip and shake the vacuum tank for 30min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-20Ga (by weight percentage, the composition is: Ga 20%, the rest is Mg) and Mg-20In (by weight percentage, the composition is: In 20%, the rest is Mg) intermediate alloys.
[0060] ③ Add Mg and Sn pure metals in the induction heating furnace, and raise the temperature to 710±5℃ in the atmosphere of protective gas. After all the additives are melted, add Mg-20Ga and Mg-20In master alloys, 2.5mm ceramic balls and 2.5mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 735±5℃ and the stirring time is 18min. After stirring, it is filtered and poured into a mold with a diameter of 300mm and a height of 800mm, and then cooled to 650±5℃.
[0061] ④ The mold is rapidly cooled to 350±5℃, then kept warm for 18 hours, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is intermittently applied at the same time. The interval time is 7 minutes, the power-on time is 4 minutes each time, and the control voltage is 200V. The ingot is kept under the internal and external temperature difference for 40 minutes, and then quickly moved to room temperature. The ingot is further heated to 330±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by extrusion at 420±5℃, with an extrusion ratio of 35:1. The profile is pre-stretched and straightened, with a total deformation of 3.5%.
[0062] ⑤ The aging treatment was set to 70±5℃ for 30h, then raised to 125±5℃ for 15h, raised to 185±5℃ for 15h, then lowered to 95±5℃ for 3.5h. The aged Mg-3.0Ga-2.0Sn-1.0In magnesium air battery anode plate was obtained.
[0063] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.71 V and the anode efficiency is 66.41%. 2 At the current density, the average discharge potential is -1.53V, and the anode efficiency is 81.01%. The corrosion rate is 0.05mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0064] Example 8 A novel green and environmentally friendly aged Mg-3.5Ga-3.5Sn-3.0In (by weight percentage, the composition is: Ga 3.5%, Sn 3.5%, In 3.0%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes of 25 mm in diameter evenly in the magnesium ingot, inject metal Ga at 38.5°C and metal In at 158.5°C into the holes respectively, and insert magnesium wire of 4 mm in diameter into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 2.9×10 -4 Pa.
[0065] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 190±5℃, keep warm for 2h, continue to heat to 395±5℃, keep warm for 1h, continue to heat to 695±5℃, keep warm for 1h, quickly flip and shake the vacuum tank for 25min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-25Ga (by weight percentage, the composition is: Ga 25%, the rest is Mg) and Mg-25In (by weight percentage, the composition is: In 25%, the rest is Mg) intermediate alloys.
[0066] ③ Add Mg and Sn pure metals in the induction heating furnace, raise the temperature to 700±5℃ in the atmosphere of protective gas, and after all the additives are melted, add Mg-25Ga and Mg-25In master alloys, 3.5mm ceramic balls and 3.5mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 730±5℃ and the stirring time is 15min. After stirring, filter and pour into a mold with a diameter of 280mm and a height of 800mm, and then cool to 640±5℃.
[0067] ④ The mold is rapidly cooled to 370±5℃, then kept warm for 20 hours, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is intermittently applied at the same time. The interval time is 8 minutes, and the power-on time is 3 minutes each time. The control voltage is 210V. The ingot is kept under the internal and external temperature difference for 30 minutes, and then quickly moved to room temperature. The ingot is further heated to 320±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by extrusion at 425±5℃, with an extrusion ratio of 30:1. The profile is pre-stretched and straightened, with a total deformation of 4%.
[0068] ⑤ The aging treatment was set to 80±5℃ for 40h, then heated to 120±5℃ for 12h, heated to 180±5℃ for 12h, then cooled to 90±5℃ for 5h. The aged Mg-3.5Ga-3.5Sn-3.0In magnesium air battery anode plate was obtained.
[0069] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.69 V and the anode efficiency is 66.15%. 2 Under the current density, the average discharge potential is -1.50V, and the anode efficiency is 80.27%. The corrosion rate is 0.09mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0070] Example 9 A novel green and environmentally friendly aged Mg-4.0Ga-2.0Sn-2.0In (by weight percentage, the composition is: Ga 4.0%, Sn 2.0%, In 2.0%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes of 28 mm in diameter evenly in the magnesium ingot, inject metal Ga at 39°C and metal In at 159°C into the holes respectively, and insert magnesium wire of 3 mm in diameter into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 2.8×10 -4 Pa.
[0071] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 180±5℃, keep warm for 3h, continue to heat to 385±5℃, keep warm for 1h, continue to heat to 685±5℃, keep warm for 1h, quickly flip and shake the vacuum tank for 20min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-20Ga master alloy (by weight percentage, the composition is: Ga 20%, the rest is Mg) and Mg-20In (by weight percentage, the composition is: In20%, the rest is Mg) master alloy.
[0072] ③ Add Mg and Sn pure metals in the induction heating furnace, raise the temperature to 700±5℃ in the atmosphere of protective gas, and after all the additives are melted, add Mg-20Ga and Mg-20In master alloys, 3mm ceramic balls and 3mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 735±5℃ and the stirring time is 20min. After stirring, filter and pour into a mold with a diameter of 290mm and a height of 800mm, and then cool to 620±5℃.
[0073] ④ The mold is rapidly cooled to 360±5℃, then kept warm for 10 hours, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is applied intermittently with an interval of 7 minutes, each power-on time of 4 minutes, and a control voltage of 140V. The ingot is kept at the internal and external temperature difference for 40 minutes, and then quickly moved to room temperature. The ingot is further heated to 330±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by extrusion at 430±5℃ with an extrusion ratio of 27:1. The profile is pre-stretched and straightened, with a total deformation of 4.5%.
[0074] ⑤ The aging treatment was set to 75±5℃ for 48h, then raised to 140±5℃ for 15h, raised to 190±5℃ for 15h, then lowered to 95±5℃ for 3h. The aged Mg-4.0Ga-2.0Sn-2.0In magnesium air battery anode plate was obtained.
[0075] The constant current discharge curve test was carried out at room temperature and pressure. 2 At the current density of 100 mA / cm, the average discharge potential is -1.73 V and the anode efficiency is 69.05%. 2 At the current density, the average discharge potential is -1.56V, and the anode efficiency is 83.36%. The corrosion rate is 0.05mg·cm according to GBT10123-2022 test at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
[0076] Example 10 A novel green and environmentally friendly aged Mg-5.0Ga-5.0Sn-3.0In (by weight percentage, the composition is: Ga 5.0%, Sn 5.0%, In 3.0%, the rest is Mg, and the content of impurity elements is controlled as follows: Fe < 0.01%, Ni < 0.01%, Cu < 0.01%) magnesium air battery anode material is prepared as follows: ① Drill holes of 30 mm in diameter evenly in the magnesium ingot, inject metal Ga at 40°C and metal In at 160°C into the holes respectively, and insert magnesium wire of 5 mm in diameter into the holes. Tighten the magnesium plug and wrap it with raw tape, then put it into a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 1.5×10 -4 Pa.
[0077] ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 200±5℃, keep warm for 4h, continue to heat to 400±5℃, keep warm for 1h, continue to heat to 700±5℃, keep warm for 0.5h, quickly flip and shake the vacuum tank for 30min, and cool it in 25±1℃ water. De-mold the completely cooled vacuum tank to obtain Mg-30Ga master alloy (by weight percentage, the composition is: Ga 30%, the rest is Mg) and Mg-30In (by weight percentage, the composition is: In 30%, the rest is Mg) master alloy.
[0078] ③ Add Mg and Sn pure metals in the induction heating furnace, raise the temperature to 710±5℃ in the atmosphere of protective gas, and after all the additives are melted, add Mg-30Ga and Mg-30In master alloys, 4mm ceramic balls and 4mm high-temperature alloy balls with a volume ratio of 1:1, and perform electromagnetic stirring. The temperature is controlled at 740±5℃ and the stirring time is 20min. After stirring, filter and pour into a mold with a diameter of 300mm and a height of 800mm, and then cool to 600±5℃.
[0079] ④ The mold is rapidly cooled to 350±5℃, then kept warm for 24 hours, quickly cooled to room temperature with water, and the mold is removed to obtain the ingot. The ingot is placed in liquid nitrogen for low-temperature treatment, and direct current is intermittently applied at the same time. The interval time is 5 minutes, and the power-on time is 5 minutes each time. The control voltage is 220V. The ingot is kept under the internal and external temperature difference for 40 minutes, and then quickly moved to room temperature. The ingot is further heated to 350±5℃, and then three multi-directional forgings are performed, with a deformation of 50% in each pass, followed by extrusion at 435±5℃, with an extrusion ratio of 30:1. The profile is pre-stretched and straightened, with a total deformation of 5%.
[0080] ⑤ The aging treatment was set to 80±5℃ for 48h, then raised to 150±5℃ for 20h, raised to 200±5℃ for 20h, then lowered to 100±5℃ for 5h. The aged Mg-5.0Ga-5.0Sn-3.0In magnesium air battery anode plate was obtained.
[0081] The constant current discharge curve test was carried out at room temperature and pressure. 2At the current density of 100 mA / cm, the average discharge potential is -1.74 V and the anode efficiency is 69.06%. 2 At the current density, the average discharge potential is -1.59V, and the anode efficiency is 84.37%. The corrosion rate is 0.12mg·cm in accordance with GBT10123-2022 at room temperature and pressure (25℃, standard atmospheric pressure). -2 ·h -1 .
Claims
1. A new green and environmentally friendly magnesium air battery anode material, It is characterized in that The composition of the anode material is as follows by weight: Ga 1.0-5.0%, Sn 0.5-5.0%, In 0-3.0%, and the rest is Mg, wherein the content of impurity elements is controlled to be: Fe<0.01%, Ni<0.01%, Cu<0.01%.
2. The novel green and environmentally friendly magnesium-air battery anode material according to claim 1, It is characterized in that The components of the anode material are as follows by weight: Ga 2.0-4.0%, Sn 1.0-2.0%, In 1.0-2.0%, and the rest is Mg.
3. A method for preparing the magnesium-air battery anode material according to claim 1 or 2, It is characterized in that The steps include: (1) Alloy preparation is carried out in an induction heating furnace. Mg and Sn are added in the form of pure metals. Under the atmosphere of protective gas, the temperature is raised to between 690 and 710 °C. After all the additives are melted, Mg-Ga master alloy and Mg-In master alloy are added. Stirring is continued. The temperature is controlled between 720 and 740 °C and the stirring time is controlled between 10 and 20 min. (2) After the stirring is completed, the mixture is poured into the mold, and the mold is further cooled to 600-650°C, and then rapidly cooled to 350-400°C, followed by insulation for 5-24 hours. After the insulation is completed, the mixture is quickly cooled to room temperature with water, and the mold is removed to obtain an ingot.
4. The method for preparing the magnesium-air battery anode material according to claim 3, It is characterized in that In the step (1), during the smelting and stirring process, ceramic balls with a size of 2 to 5 mm and high-temperature alloy balls with a size of 2 to 5 mm are added, and the two kinds of balls are mixed in a volume ratio of 1:
1. Before adding, they are cleaned by ultrasonic-alcohol to remove surface dust, and then dried and heated to 300°C.
5. The method for preparing the magnesium-air battery anode material according to claim 4, It is characterized in that In the step (1), the melt is stirred rapidly by electromagnetic stirring, and after stirring, the melt is filtered to completely separate the added small balls, and then poured into a mold with a diameter of 250-300 mm and a height of 700-900 mm.
6. The method for preparing the magnesium-air battery anode material according to claim 3, It is characterized in that The preparation method of the Mg-Ga master alloy or the Mg-In master alloy comprises the following steps: ① Drill holes with a diameter of 10-30 mm evenly in the magnesium ingot, heat the metal Ga to 30-40°C or heat the metal In to 150-160°C, and inject it into the hole. At the same time, plug the hole with a magnesium wire with a diameter of 3-5 mm, tighten the magnesium plug, and wrap the raw tape between the magnesium plug and the magnesium ingot to prevent Ga or In from leaking out. Then put it in a sealable steel can, evacuate it and seal it. The vacuum degree is controlled at 10 -3 ~10 -4 Between Pa; ② Place the vacuum tank in an induction heating furnace, set the heating rate to 15℃ / min, heat to 180~200℃, keep warm for 1~5h, continue to heat to 350~400℃, keep warm for 0.5~1h, continue to heat to 650~700℃, keep warm for 0.5~1h, quickly turn the vacuum tank over and shake it for 10~30min, and cool it in 25±1℃ water; ③ The completely cooled vacuum tank is demolded to obtain a Mg-Ga intermediate alloy or a Mg-In intermediate alloy.
7. The method for preparing the magnesium-air battery anode material according to claim 3, It is characterized in that The following steps are also included: (3) Place the ingot in liquid nitrogen for low-temperature treatment, and apply direct current intermittently. The intermittent time is controlled within 5-10 minutes, and the power-on time each time does not exceed 5 minutes. The voltage is controlled between 100-220V. Keep the ingot under the temperature difference between the inside and outside for 30-60 minutes, and then quickly move it to room temperature. (4) The ingot is further heated to between 200 and 350°C, and then multi-directional forging is performed, followed by direct extrusion to obtain an extruded material.
8. The method for preparing the magnesium-air battery anode material according to claim 7, It is characterized in that The extruded material is a plate or a rod.
9. The method for preparing the magnesium-air battery anode material according to claim 7, It is characterized in that The extruded material is a plate, which is subsequently rolled, with the plate temperature controlled at 150-300°C, the rolling reduction controlled between 30-80%, the roller temperature controlled at 70-100°C during the rolling process, and graphite powder or molybdenum disulfide applied on the rolling surface to achieve a lubrication effect.
10. The method for preparing the magnesium-air battery anode material according to claim 7, It is characterized in that The deformed material is further subjected to aging treatment, including the following steps: (5) Pre-stretch and straighten the profile, control the total deformation between 3% and 5%, and pre-stretch the profile by 10% to 15% of the yield strength, then conduct power treatment, alternately load the profile with pulse current and direct current, and control the alternating loading time between 10 and 30 minutes; (6) Then carry out aging treatment, the system is to keep the temperature at 60~80℃ for 24~48h, then increase the temperature to 120~150℃ and keep it for 10~20h, increase the temperature to 180~200℃ and keep it for 10~20h, then cool down to 90~100℃ and keep it for 3~5h; (7) For the plate, a final cold pressing deformation is performed to control the shape of the plate, and the deformation is controlled between 1 and 3%, and then it is rolled.
